The ruling coalitions in the Republic of Moldova after the “Twitter Revolution” – the policy of integration or desintegration? - Sikora-Gaca, Małgorzata (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
In 2009, the Republic of Moldova created an alternative to the communist leadership. In 2013, the Alliance for European Integration was replaced by the Alliance for Pro-European Governance, which secured two issues: the signing of the Association Agreement between the Republic of Moldova and the European Union, and the interests of local oligarchs. After the parliamentary elections in 2014, as an alternative to the increasingly powerful Igor Dodon’s Party of Socialists, another coalition, the Political Alliance for European Moldova was created and ‘sealed’ by embezzling $ 1 billion from Moldovan banks (12.5% of GDP). The coalition formed in January 2015, was replaced by the re-launched Alliance for European Integration, and then by another coalition without a definite name in January 2016. This extremely expanded political activity is a backdrop for the façade of democracy and the subsequent parliamentary elections scheduled for 2018. The pro-European coalitions in the Republic of Moldova discredited themselves in front of the society as strongly as their predecessors (the communists), causing a state of general disintegration.

W 2009 roku stworzono w Republice Mołdawii alternatywę dla komunistycznego przywództwa. W 2013 roku, w miejsce „Sojuszu na rzecz Integracji Europejskiej” powołano „Koalicję na rzecz Rządów Proeuropejskich”, co zabezpieczyło dwie kwestie: podpisanie umowy stowarzyszeniowej między Republiką Mołdawii a Unią Europejską oraz interesy lokalnych oligarchów. Po wyborach parlamentarnych w 2014 roku alternatywą dla rosnącej w siłę Partii Socjalistów Igora Dodona stała się kolejna z koalicji „Sojusz polityczny na rzecz Europejskiej Mołdawii”, „przypieczętowana” defraudacją 1 mld USD z mołdawskich banków (12,5% PKB). Powołana w styczniu 2015 roku koalicja już w lipcu tego samego roku została zastąpiona przez ponownie zainicjowany do życia „Sojusz na rzecz Integracji Europejskiej”, a w styczniu 2016 roku przez kolejną z koalicji, bez bliżej określonej nazwy. Ta niezwykle rozbudowana działalność polityczna jest tłem dla fasadowej demokracji i kolejnych wyborów parlamentarnych zaplanowanych w 2018 roku. Koalicje proeuropejskie w Republice Mołdawii skompromitowały się przed społeczeństwem równie mocno jak poprzednicy (komuniści), wywołując stan ogólnej dezintegracji.
Koalicje rządzące w Republice Mołdawii po „rewolucji twitterowej” – polityka integracji czy dezintegracja?
Keywords: Moldova; pro-European coalition; corruption; parliamentary elections in the Republic of Moldova in 2018; Mołdawia; koalicja proeuropejska; korupcja; wybory parlamentarne w Republice Mołdawii w 2018 roku